The role of hematological parameters in differentiating Plasmodium falciparum and others – a study from Somalia - Özdemir, Serdar; Algın, Abdullah; Altunok, İbrahim; Ebubekir, Arslan (Publishing Office of the University of Rzeszow, 2022)
Introduction and aim. Accurate identification of Plasmodium species is important because of the differences in their treatment. We aimed to investigate the role of hematological and biochemical parameters in the differentiation of Plasmodium falciparum and other plasmodium species. Material and methods. This is a retrospective study. Patients admitted to the emergency department with signs and symptoms of malaria were included into the study. Patients with malaria were grouped as P. falciparum and others. Hematological parameters of two groups were compared by univariate and multivariate analysis. Statistical analysis was performed using the Jamovi. Results. A total of 107 patients were included in the study. According to univariant and multivariant analysis there was no difference in between two groups in the terms of blood urea nitrogen, aspartate aminotransferase, total bilirubin, hemoglobin, hematocrit, white blood cell count, platelet count, and mean platelet volume (in univariate analysis p values were 0.029, 0.011, 0.019, 0.171, 0.870, 0.307, 0.042, and 0.276, respectively and in multivariate analysis p values for blood urea nitrogen, aspartate aminotransferase, total bilirubin, hemoglobin, and platelet count were 0.100, 0.535, 0.328, and 0.213, respectively). Conclusion. The investigated hematological and biochemical parameters were found to be not valuable in predicting type of malaria. On the other hand, we recommend confirming the results of our study with larger samples and multicenter studies.
Study was approved by the institutional review board, and a waiver of authorization was given (Ethics Committee decision no. 450, date: 11.22.2021).
Keywords: malaria; Plasmodium falciparum; Plasmodium vivax; platelets